OTEC Potential Studies For Energy Sustainability In Riau Islands - Ibnu Kahfi Bachtiar; Risandi Dwirama Putra (IAES Indonesia Section, 2019)
Interest in the use of alternative renewable energy resources has been developed recently due to increased energy consumption and depletion of fossil fuel reserves. A major concern the world to reduce is dependence impact from fossil fuel consumption with renewable energy. Renewableenergy sources have enormous economic, environmental benefits and provide energy security. The most potential renewable energy sources of ocean energy include Ocean Thermal Energy Conversion (OTEC). OTEC is a technology to generate electricity using a heat source thermal energy stored in the sea and is becoming increasingly attractive option to supply additional energy for many tropical countries and islands such as Riau Islands. Two monitoring stations were collected in Bintan Island using CTD. CTD profiler allows to the determination of derived and relevant quantities in situ measurement ocean temperature per depth. The relationship between ocean temperature and ocean depth represented with Regression Model Fit Analysis (RMFA). RMFA models to estimates ocean temperature profiles from CTD measurements. To predict ocean depths up to 2000 meters using Equation of State Model (EoSM) of ocean water. The OTEC efficiency value can be calculated using the equation of Carnot efficiency (η). Carnot efficiency maximum in Riau Island is η <0.7.